2019
DOI: 10.1111/pan.13757
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational cohort study on the incidence of postoperative sore throat in the pediatric population

Abstract: Background: Postoperative sore throat is common after general anesthesia. The incidence in pediatric anesthesia is variable, and the etiology unclear. Establishing risk factors would enable prevention and could improve quality of care. Aims:We performed a prospective single-center cohort study aiming to establish the incidence of postoperative sore throat in children undergoing GA with an endotracheal tube or laryngeal mask airway. Secondary aims were to identify independent risk factors for sore throat and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
3
11
1
Order By: Relevance
“…In our study, there was a greater incidence of postoperative complications, such as nausea and sore throat, with ETT. Additionally, previous studies [3,8,12] reported that ETT was associated with a greater incidence of sore throat (13.3-54.7%) than LMA; our nding was consistent with those of previous studies. In our study, we did not observe laryngospasm and aspiration in all cases; however, such complications were reported in previous studies [5,8,12].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there was a greater incidence of postoperative complications, such as nausea and sore throat, with ETT. Additionally, previous studies [3,8,12] reported that ETT was associated with a greater incidence of sore throat (13.3-54.7%) than LMA; our nding was consistent with those of previous studies. In our study, we did not observe laryngospasm and aspiration in all cases; however, such complications were reported in previous studies [5,8,12].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of POST in children is varied from study to study, with a range of 3.3% to 50.7% in studies performed in developed countries. 10 , 11 A study done in England in 2019 found the incidence of POST was 36.5% among pediatrics undergoing surgery under general anesthesia. 11 Children have a high risk of developing POST since they have relatively smaller airways and lower mucosal perfusion pressure compared to adults, the likelihood of mucosal hypo perfusion and subsequent edema caused by airway instrumentation and cuff hyperinflation would be exaggerated in children.…”
Section: Introductionmentioning
confidence: 99%
“…A postoperative sore throat will result in delayed oral intake, and patient dissatisfaction, and it affects patients’ well-being after surgery during the immediate postoperative period. 11 , 13 One study shows that 30% of pediatric patients reporting a sore throat had delayed oral intake due to difficulty in swallowing, with no statistical difference between ETT and LMA use. 11 The delayed oral intake on the other hand will result in dehydration and can progress to delayed wound healing and increased hospital stay and increased cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] POST has a chance to persist for several days and may lead to potential dissatisfaction in patients after operations. [5][6][7][8] It can also cause children to delay intake [9] or cause patients to have longer postoperative stays after surgery. [10] In the past few years, there have been some ways to improve PONV in enhanced recovery after surgery (ERAS) [11] ; we believe that there is room for improving ERAS pathways for POST.…”
Section: Introductionmentioning
confidence: 99%